Services trade and infrastructure development: Evidence from African countries - Kabiru Hannafi Ibrahim; Rossanto Dwi Handoyo; Wasiaturrahma Wasiaturrahma; Tamat Sarmidi (Cogent Economics & Finance)
Using a dynamic system GMM estimate, this study analyzed the impact of services trade on the development of infrastructure in 38 African countries over the period 2000–2020. Telecommunications, trade/transport-related, and port infrastructures were modelled as the dependent variables on services trade openness. Other sets of control variables include real GDP, financial development, gross fixed capital formation, external debt, population density, urbanization, exchange rate, and services value-added. Our empirical strategy revealed that regardless of the infrastructure indicator used in the estimate, services trade, GDP, financial development, external debt, and services value-added significantly promote the development of infrastructure in the continent. Capital formation increases trade/transport-related and reduces port infrastructure while population density increases trade/transport-related and port infrastructure. The finding further indicates that urbanization increases telecommunications and reduces trade/transport-related infrastructure. The exchange rate reduces the development of telecommunications and port infrastructure. The findings are therefore vital to present policies related to services trade and infrastructure development in African countries.